2007
DOI: 10.1523/jneurosci.3395-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Two Distinct Heterotypic Channels Mediate Gap Junction Coupling between Astrocyte and Oligodendrocyte Connexins

Abstract: Genetic diseases demonstrate that the normal function of CNS myelin depends on connexin32 (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
203
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(213 citation statements)
references
References 65 publications
7
203
3
Order By: Relevance
“…46 By studying the temporal relationship between astrocyte and myelin loss, we showed that astrocyte death precedes demyelination. Connexins connect astrocytes to each other and to oligodendrocytes in a network termed the "glial syncytium," and the integrity of this network is crucial for normal CNS functions, 26,[47][48][49] such as myelination and remyelination upon demyelinative injury. 11,13,25 The importance of the glial syncytium for myelination has been shown in studies utilizing genetic deletions of connexins 43 and 47.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…46 By studying the temporal relationship between astrocyte and myelin loss, we showed that astrocyte death precedes demyelination. Connexins connect astrocytes to each other and to oligodendrocytes in a network termed the "glial syncytium," and the integrity of this network is crucial for normal CNS functions, 26,[47][48][49] such as myelination and remyelination upon demyelinative injury. 11,13,25 The importance of the glial syncytium for myelination has been shown in studies utilizing genetic deletions of connexins 43 and 47.…”
Section: Discussionmentioning
confidence: 99%
“…13,25 In the CNS, Cx43 expression is restricted to astrocytes and couples with Cx47, which is only present in oligodendrocytes. 26 Impairment of heterotypic Cx43:Cx47 gap junctions by deleting one of the partners results in myelin pathology 22 . We studied Cx43 gene expression and found that it was substantially downregulated 12 hours after hyponatremia correction (P Ͻ 0.001 compared with controls).…”
Section: Early Downregulation Of Astrocyte-oligodendrocyte Gap Junctimentioning
confidence: 99%
“…Astrocytic Cx43 depletion decreases glucose concentration in the extracellular medium and inhibits OPC proliferation, which can be compensated by glucose supply Cx43 is highly expressed by astrocytes, and works as hemichannels and/or homomeric gap junction channels (Cx43-Cx43) between astrocytes (Evans et al, 2013;Mitterauer, 2015;Ransom and Giaume, 2013;Ye et al, 2009), and also forms heteromeric gap junctions (Cx43-Cx47) between astrocytes and oligodendrocytes (Orthmann-Murphy et al, 2007;Theis et al, 2005). It has been reported that in astrocytes, Cx43 deletion increases glucose uptake by a compensatory upregulation of Glut transporters and/or glucose metabolism enzymes (Gangoso et al, 2012).…”
Section: Inhibition Of Hemichannel Activity Impacts Opc Proliferationmentioning
confidence: 99%
“…18,19 The O/A coupling is mediated by heterotypic channels between CÂ47/CÂ43 and CÂ32/CÂ30, both appearing to be essential for the proper maintenance of myelin. 20 So far, CÂ47 mutants have been shown to result in loss of function, suggesting an impaired O/A coupling mediated by CÂ47/CÂ43. 21 Here, we provide further evidence that loss of CÂ47 function causes PMLD.…”
Section: Introductionmentioning
confidence: 99%